A Case Study of Cefuroxime/Oxcarbazepine Induced Stevens - Johnson Syndrome - Abraham, Tanisha.; N, Kiran.; R. Hiremath, Shobha Rani; S.V, Jaiprakash; Pais, Nalini. (Indian Journal of Pharmacy Practice)
Any prescribed medication for any patient can cause adverse effects which sometimes can be life threatening. So, 1 responsibility lies on the health care professionals to be cautious while prescribing for their patients . They must be asked for history of any drug allergies and instruct them to report immediately if any side effects occur. This is particularly important for a few categories of drugs like NSAIDs, antibiotics like penicillin's, cephalosporin's, and anticonvulsants like diphenylhydantoin and carbamazepine. These are well known to cause severe drug reactions 2,3 like Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN). SJS and TEN is a potentially fatal condition that can manifest with severe skin and mucosal reaction. It also involves other sites of mucosal involvement like in the eyes and vaginal mucosa. There are no strict guidelines available for treating SJS or TEN. 4 Use of steroidal agents to treat these conditions is still a controversy. According to the epidemiological studies 5,6,7 published, the average mortality rate for SJS was estimated to be about 1-5% and TEN to be about 25-35%. Superimposed infections and severe mucosal involvement are more often associated with higher mortality. Therefore, isolating the patient to an aseptic area could be the primary step for managing these conditions along with good nursing, which can reduce the open skin lesion infection and can contribute to a fast recovery